Racist and Anti-diversity Attitudes as Predictors of Support for Political Violence among Supporters of Mainstream Political Parties - Vergani, Matteo (Terrorism and political violence, 2023)
Although there are widespread concerns about support for political violence among people affiliated with mainstream political parties, this topic remains largely under-researched. This article examines the relationship between the respondents’ support for political violence and their endorsement of social and political positions that are highly divisive between the left and the right. We collected survey data from a sample of 4,019 respondents from Victoria (Australia). Our analyses distinguished between people affiliated with left-wing parties, right-wing parties, and people with no party affiliation, and found that support for racist and anti-diversity positions is significantly associated with support for political violence across the three groups. Specifically, having negative attitudes to ethnic and religious minorities and having negative attitudes to diversity are significant predictors of support for political violence in the right-wing group. Having negative attitudes to diversity is a predictor of support for political violence in the left-wing group. Having anti-Muslim prejudice is a predictor of support for political violence among people with no party affiliation. Other significant predictors are having anti-democratic views (across the three groups) being male and being young (in the left-wing and right-wing groups) and having experienced discrimination (in the the left-wing group).